2021
DOI: 10.3389/fimmu.2021.652007
|View full text |Cite
|
Sign up to set email alerts
|

Beyond First-Line Immune Checkpoint Inhibitor Therapy in Patients With Hepatocellular Carcinoma

Abstract: Until recently, the treatment landscape for hepatocellular cancer (HCC) was dominated by tyrosine kinase inhibitors (TKIs) which offered an overall survival (OS) benefit when used both in the first-and second-line setting compared to best supportive care. However, the treatment landscape has changed with the introduction of immune checkpoint inhibitors (ICIs) for the treatment of HCC with significant improvement in OS and progression free survival reported with combination atezolizumab and bevacizumab compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Although the results are encouraging, treatment resistance and non-response is a concern ( Dong et al, 2020 ). One of the potential reasons for these discordances could be due to the involvement of other dominant immunoregulatory molecules that play along with PD-L1/PD1 pathway in HCC microenvironment ( Lafleur et al, 2018 ; Heinrich et al, 2020 ; Sharma and Motedayen Aval, 2021 ). Our recent work has identified that PD-L1 is the only molecule in B7 family which exhibits a high correlative expression with tryptophan degrading enzyme, IDO in HCC ( Chinnadurai et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the results are encouraging, treatment resistance and non-response is a concern ( Dong et al, 2020 ). One of the potential reasons for these discordances could be due to the involvement of other dominant immunoregulatory molecules that play along with PD-L1/PD1 pathway in HCC microenvironment ( Lafleur et al, 2018 ; Heinrich et al, 2020 ; Sharma and Motedayen Aval, 2021 ). Our recent work has identified that PD-L1 is the only molecule in B7 family which exhibits a high correlative expression with tryptophan degrading enzyme, IDO in HCC ( Chinnadurai et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of multiple genes has to date largely focused on augmentation of T cell activation. However, NK cells are also present within tumours, and their number correlates with the outcome and promotes adaptive immunity [6,119] . Thus, the expression of genes targeting NK cells could generate a broader local cellular immune response whilst simultaneously reducing the toxicities and off-target effects associated with systemic therapies.…”
Section: Insertion Of Transgenes To Enhance the Anti-tumour Nk Cell Responsementioning
confidence: 99%
“…Antibody-mediated targeting of inhibitory receptors (checkpoints) has proved therapeutically useful in a number of cancer settings, with the recent approval of an anti-PDL1 antibody for treating HCC [ 120 ] . In the context of OV therapy, the combination of checkpoint inhibitors with OVs is a promising approach under investigation.…”
Section: Modifying Oncolytic Virus Therapy To Enhance Nk Cell Responsesmentioning
confidence: 99%
“…In view of this, ramucirumab was included in the second-line therapy in the 2019 NCCN guidelines (15). However, low objective response rates (ORRs), an improvement in OS of only 2-3 months, resistance, and cancer progression after standard treatment, regardless of firstand second-line settings, were observed, and therefore, more efficacious therapeutics should be explored (18).…”
Section: Introductionmentioning
confidence: 99%